2017
DOI: 10.1186/s12910-017-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

Defining reasonable patient standard and preference for shared decision making among patients undergoing anaesthesia in Singapore

Abstract: BackgroundA cross-sectional study to ascertain what the Singapore population would regard as material risk in the anaesthesia consent-taking process and identify demographic factors that predict patient preferences in medical decision-making to tailor a more patient-centered informed consent.MethodsA survey was performed involving patients 21 years old and above who attended the pre-operative evaluation clinic over a 1-month period in Singapore General Hospital. Questionnaires were administered to assess patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Numerous studies have suggested that demographic factors, such as ethnicity, age and gender, influenced an individual's perception of an adverse outcome. (16) Our study identified various subgroups with more concerns for certain adverse outcomes: younger patients (orodental trauma); government-subsidised patients (sore throat); previous anaesthesia experience (sore throat); women (nausea); previous post-anaesthesia adverse outcomes (sore throat); and less than six years of education (nausea and somnolence). However, the statistically significant differences in ranking did not translate into differences in terms of patients' willingness to pay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have suggested that demographic factors, such as ethnicity, age and gender, influenced an individual's perception of an adverse outcome. (16) Our study identified various subgroups with more concerns for certain adverse outcomes: younger patients (orodental trauma); government-subsidised patients (sore throat); previous anaesthesia experience (sore throat); women (nausea); previous post-anaesthesia adverse outcomes (sore throat); and less than six years of education (nausea and somnolence). However, the statistically significant differences in ranking did not translate into differences in terms of patients' willingness to pay.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10) However, research thus far has largely been centred on the Western population, limiting the transferability of results to the Singapore population, where differences in culture, socioeconomics and healthcare structure have an undeniable influence on patient's perspectives, expectations of care and health-seeking behaviour. (11)(12)(13)(14)(15)(16) Furthermore, significant difference exists between the willingness-to-pay (WTP) spending habits between Asians and Westerners. Asians are more willing to pay to avoid negative emotions but less willing to do so to experience positive emotions, while Western populations have reported converse results.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of postsurgical 30-day mortality risk is an important clinical outcome that is of interest to both surgeons and patients and therefore aids in shared decision making. 26 Thirty-day all-cause postoperative mortality is a widely accepted, valid and relevant outcome measure of surgical care. 27 For this study, the postoperative mortality data were synced with the National Registry of Death data, ensuring the integrity and completeness of the data.…”
Section: Discussionmentioning
confidence: 99%
“…16 Patients prefer this decision-making model compared with, for example, having to decide on their own, or the anaesthesiologist paternalistically deciding for them. 17 The HPCSA booklets on ethical conduct have the general title 'Guidelines for Good Clinical Practice in the Healthcare Professions' . Guidelines normally have a somewhat lower hierarchical status than laws in that they are not normally legally enforceable.…”
Section: Regulatory Requirementsmentioning
confidence: 99%